2022
DOI: 10.3389/fdgth.2022.842301
|View full text |Cite
|
Sign up to set email alerts
|

Voice Analysis for Neurological Disorder Recognition–A Systematic Review and Perspective on Emerging Trends

Abstract: Quantifying neurological disorders from voice is a rapidly growing field of research and holds promise for unobtrusive and large-scale disorder monitoring. The data recording setup and data analysis pipelines are both crucial aspects to effectively obtain relevant information from participants. Therefore, we performed a systematic review to provide a high-level overview of practices across various neurological disorders and highlight emerging trends. PRISMA-based literature searches were conducted through PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 94 publications
1
12
0
1
Order By: Relevance
“…Studies have found differences between the voices of depressed and healthy people ( 22 ), and acoustic features are correlate with the severity of depressive symptoms and their variability ( 23 ). Several acoustic features are thought to correlate with depression ( 24 ), Machine Learning and Deep Learning techniques have been widely used in the studies of voice analysis ( 25 ). For the audio recordings in this study, we also performed some voice analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found differences between the voices of depressed and healthy people ( 22 ), and acoustic features are correlate with the severity of depressive symptoms and their variability ( 23 ). Several acoustic features are thought to correlate with depression ( 24 ), Machine Learning and Deep Learning techniques have been widely used in the studies of voice analysis ( 25 ). For the audio recordings in this study, we also performed some voice analysis.…”
Section: Discussionmentioning
confidence: 99%
“…., t N . For the squared error loss L(y i , γ l (t i )) = L(y i − γ l (t i )) 2 the solution corresponds to the natural polynomial spline, see discussion in [64]. Hence, we have been able to motivate the spline representation of the IMF as the solution to a generalised estimation problem in an RKHS regularised function space.…”
Section: Spline Representations Of An Imf and Reproducing Kernel Hilb...mentioning
confidence: 96%
“…These are repeating syllables, spontaneous dialogue, improvised description of a figure, etc. [ 2 ]. An ASR system can use several speech features descriptive of the different phases of speech production process, extensively reviewed by [ 2 , 4 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations